El karst del Pico del Castillo de Acher (Pirineo Occidental, Huesca): factores condicionantes de su distribución - Julián Andrés, Asunción (Geographicalia, 2017)
In the summit area of the Castillo de Acher Peak (Western Pyrenees,Huesca) many exokarstic morphologies have been developped, affecting mos tof its surface. In this work, the different types of morphologies identified (dolines and karren forms) are analyzed, as well as the geological and climatological factors that aid in its formation. On the other hand, a detailed study of the spatial distribution pattern of these morphologies, and its determining causes, is made.
Keywords: Castillo de Acher; Aragonese Pyrenees; exokarstic landforms; spatial distribution.